Comparison of Adaptive Ant Colony Optimization for Image Edge Detection of Leaves Bone Structure - Liantoni, Febri; Perwira, Rifki Indra; Bataona, Daniel Silli (Politeknik Elektronika Negeri Surabaya (PENS), 2018)
Leaf bone structure has a characteristic that can be used as a reference in digital image processing. One form of digital image processing is image edge detection. Edge detection is the process of extracting edge information from an image. In this research, Adaptive Ant Colony Optimization algorithm is proposed for edge image detection of leaf bone structure. The Adaptive Ant Colony Optimization method is a modification of Ant Colony Optimization, in which the initial an ant dissemination process is no longer random, but it is done by a pixel placement process that allows for an edge based on the value of the image gradient. As a comparison also performed edge detection using Robert and Sobel method. Based on the experiments performed, Adaptive Ant Colony Optimization algorithm is capable of producing more detailed image edge detection and has thicker borders than others.Â Keywords: edge detection, ant colony optimization, robert, sobel